Prevalence and risk factors associated with postnatal depression in a South African primary care facility - Nyundu S.J. Phukuta; Olufemi B. Omole (AOSIS, 2020)
Background: The prevalence and factors that influence postnatal depression (PND) vary according to context. Aim: To determine the prevalence and factors associated with PND in the postnatal clinic of a large community health centre. Setting: This study was conducted at Levai Mbatha Community healthcare centre, in Evaton, South of Gauteng. Method: In a cross-sectional study, the Edinburg Postnatal Depression Scale (EPDS) was administered on 227 consecutive mothers during postnatal clinic visits. In addition, sociodemographic and clinical information were collected. Analysis included descriptive statistics, chi-square test and logistic regression. A score of greater than 13 on the EPDS screened positive for PND. Results: Participants' mean age was 27 years, and most completed less than grade 12 education (52.4%), were single (55.5%), were employed or had a working partner (60%) and had no previous PND (97%). The proportion of participants screening positive was 38.8%. In the adjusted logistic regression, completing only primary school education (odds ratio [OR]: 9.11; 95% confidence interval [CI]: 1.03-80.22; p = 0.047), using contraceptive prior to index pregnancy (OR: 2.05; 95% CI: 1.12-3.72; p = 0.019) and reporting a thought of self-harm or infanticide (OR: 7.08; 95% CI: 5.79-22.21; p = 0.000) significantly increased the risk of PND. In contrast, having a relationship with the father of the index child (OR: 0.42; 95% CI: 0.18-0.94; p = 0.037) mitigated this risk. Conclusion: The proportion of women screening positive for PND was high in the study setting and was concomitant with significant risk of suicide or infanticide. This highlights the need to screen and consider PND as a vital sign during postnatal visits, especially in the face of low educational attainment, failed contraception and poor or no relationship with the father of the index child.